The beta secretase BACE1 regulates the expression of insulin receptor in the liver - Paul J. Meakin (Nature Portfolio, 2018)
A soluble form of insulin receptor in human plasma has been previously reported. Here the authors demonstrate that insulin receptor is cleaved by BACE1 that can regulate biological active insulin receptor levels in a glucose concentration-dependent manner, both in physiological and diabetic conditions.